CORRELATION OF PSA, PV, AND IPP IN DETECTING BOO CAUSED BY PROSTATE ENLARGEMENT - Kurnia, Indra Cahya; Ghinorawa, Tanaya; Rochadi, Sungsang (Indonesian Journal of Urology, 2014)
Objective: To define the relationship between intravesical prostatic protrusion (IPP), prostate specific antigen (PSA), and prostate volume (PV), and to determine which one is the best predictor of bladder outlet obstruction (BOO) due to benign prostatic enlargement. Material & method: 95 male patients > 40 years old presenting with LUTS and BPH, between January until July 2012. They were evaluated with digital rectal examination (DRE), International Prostate Symptoms Score (IPSS), total PSA serum, uroflowmetry, post-void residual urine measurement, IPP and PV using transabdominal ultrasound. Statistical analysis included Chi-square and Spearman’s Rank correlation test.Receiver Operator Characteristic (ROC) curves were used to evaluate the correlation of PSA, PV, and IPP with BOO. Results: Mean PSA was significantly higher in obstructed patients (8.6 ng/mL; 0.76-130) compared to non-obstructed patients (6.44 ng/mL; 1.0-40.6). Mean PV was significantly larger in obstructed patients (50.33 mL ± 24.34) compared to non-obstructed patients (45.39 mL ± 23.43). Mean IPP was significantly greater in obstructed patients (7.29 ± 2.78) compared to non-obstructed patients (6.59 ± 2.93). The Spearman rho correlation coefficients were 0.617, 0.721, and 0.797, for PSA, PV, and IPP, respectively. Using ROC curves, the areas under the curve for PSA, PV, and IPP were 0.509, 0.562 and 0.602, respectively. The positive predictive values of PV, PSA, and IPP were 59.7%, 55.6% and 60.2% respectively. Conclusion: PSA, PV, and IPP measured through transabdominal ultrasonography are noninvasive and accessible method that significantly correlates with BOO in BPH patients. IPP is a better predictor for BOO than PSA or PV.Keywords: Bladder outlet obstruction, intravesical prostatic protrusion, prostate specific antigen, prostate volume, transabdominal ultrasound, benign prostate hyperplasia.